Sporophytic apomixis in polyembryonic Handroanthus serratifolius (Vahl) SO Grose (Bignoniaceae) characterizes the species as an agamic polyploid complex - Alves, Mariana F.; Duarte, Mariana O.; Bittencourt, Nelson S. [UNESP]; Oliveira, Paulo E.; Sampaio, Diana S. (Springer, 2016)
Neopolyploidy has been associated with gametophytic apomixis and breakdown of gametophytic self-incompatibility. Nevertheless, Bignoniaceae presents agamic polyploid complexes with neopolyploidy associated to sporophytic apomixis. Apomictic populations are commonly polyploid, polyembryonic and self-fertile, while diploids are mostly late-acting self-incompatible (LSI) and monoembryonic. Contrastingly, Handroanthus serratifolius shows hexaploid monoembryonic and polyembryonic populations, although breeding system has been studied only for monoembryonic individuals, which are LSI. Our aim here was to investigate breeding system and early embryology in polyembryonic individuals of H. serratifolius to define if they form an agamic polyploid complex. Experimental pollinations and histological analyzes of ovules and young seeds were carried out. Megasporogenesis and megagametogenesis occurred as in other sexual species of Bignoniaceae. The polyembryonic individuals were self-fertile and double fertilization was observed both after self and cross-pollinated pistils. Adventitious embryos originated from the hypostasis and integument of the ovule, indicating sporophytic apomixis. Adventitious embryo precursor cells occurred in all pistils, including unpollinated ones. But unpollinated pistils aborted possibly due to absence of endosperm, and pollination was required for fruit-set (pseudogamy). It is possible that the self-fertility in polyembryonic individuals ensues as the initial endosperm of self-fertilized ovules supply early adventitious embryos development, and these embryos would later prevent the abortion of selfed pistils. The sporophytic apomixis in polyembryonic populations and the occurrence of sexual monoembryonic populations of H. serratifolius allows us to consider the species part of an agamic polyploid complex. But in contrast with other Handroanthus agamic complexes, both apomictic and sexual LSI plants were hexaploid.
Keywords: Megagametogenesis; Megasporogenesis; Neopolyploidy; Polyembryony; Pseudogamy; Self-fertility